Crystal growth and scintillation properties of YAG:Ce 3+ for γ and α detection - Min Jeong Kim (2019)
© 2018 Elsevier Ltd A bulk single crystal of yttrium aluminum garnet (Y 3 Al 5 O 12 :Ce 3+ , YAG:Ce 3+ ) with good optical quality and free of cracks has been grown successfully by the Kyropoulos method. The dimension of the as grown crystal boule was Ø 20 × 30 cm 3 . The cut and polished crystal sample of dimensions 1 × 1 × 0.5 cm 3 was used for further measurements. The phase purity was confirmed by powder X-ray diffraction pattern analysis. The scintillation properties, such as X-ray emission spectrum, pulse height spectra, energy resolution, and scintillation decay time, were investigated using a 137 Cs γ-ray source. The recorded X-ray emission spectrum shows a broad band between 500 and 700 nm with a peak at around 540 nm, which is attributed to the 5d-4f transition of the Ce 3+ ion. The pulse-shape discrimination (PSD) of α and γ signals in a YAG:Ce 3+ crystal has been studied by using different pulse shapes. The grown YAG:Ce 3+ crystal which is non-hygroscopic, chemically inert, fast inorganic scintillator could be used for radiation detection application in nuclear, and high energy physics.